2017
DOI: 10.3892/ijmm.2017.3350
|View full text |Cite
|
Sign up to set email alerts
|

Petasites japonicus bakkenolide B inhibits lipopolysaccharide‑induced pro‑inflammatory cytokines via AMPK/Nrf2 induction in microglia

Abstract: Abnormal neuroinflammatory responses have diverse roles in neuronal death, oxidative stress and neurodegenerative diseases, such as Alzheimer's and Parkinson's disease. Microglia regulate these responses via molecular signaling cascades that involve inflammatory cytokines and complement proteins. Bakkenolide B from Petasites japonicus exhibits significant anti‑inflammatory and anti‑allergic bioactivities. The present study investigated the anti‑neuroinflammatory effects and underlying molecular mechanisms of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…For example, AMPK mediates the amplified activation of Nrf2 signaling to inhibit the lung inflammatory response caused by smoking and ultimately improve chronic obstructive pulmonary disease [ 55 ]. In addition, activation of AMPK/Nrf2 signaling pathway can also inhibit neuroinflammation in neurodegenerative diseases [ 56 ]. Our study proved that the AMPK/Nrf2 pathway was suppressed in STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, AMPK mediates the amplified activation of Nrf2 signaling to inhibit the lung inflammatory response caused by smoking and ultimately improve chronic obstructive pulmonary disease [ 55 ]. In addition, activation of AMPK/Nrf2 signaling pathway can also inhibit neuroinflammation in neurodegenerative diseases [ 56 ]. Our study proved that the AMPK/Nrf2 pathway was suppressed in STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is a major downstream signaling molecule activated by APPL1 and has been demonstrated by studies on adiponectin-dependent AMPK signaling. A recent study suggested that bakkenolide B inhibited lipopolysaccharide-induced pro-inflammatory cytokines via AMPK activation in microglia [ 44 ]. In our study, administration of rCTRP9 markedly increased the expression of p-AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…Bakkenolide B Bakkenolide B is a natural substance obtained from the Petasites japonicus plant which has been shown to suppress both inflammatory and allergic responses. Treatment with bakkenolide B reduced production of microglia, IL-1b, IL-6, IL-12, and TNFa [73].…”
Section: Currently Proposed Treatmentsmentioning
confidence: 94%